Assessing the degree of involvement of Kazakhstani industries in global value chains (Journal of Economic Research & Business Administration, 2023)
The economy structure, availability of resources and production capacities generally define the involvement of country’s goods in global production chains. This research aims to evaluate the degree of global value chain (GVC) involvement for Kazakhstani industries for understanding the country's integration into the global economy and its competitiveness in international markets.The evaluation of the involvement of Kazakhstani goods in GVCs incorporates widely acknowledged indicators of forward and backward integrations introduced by World Bank experts. This analysis delves into the causal relationships within the demand model, providing insights into the intricacies of Kazakhstani goods' integration into production chains. The results revealed that Kazakhstan's participation in GVCs is predominantly driven by forward participation. The peak of GVC involvement occurred during 2004-2008, with total participation exceeding 45%, particularly in sectors like mining, energy production, rubber and plastic products, and base metals. While the role of the country as a global provider of commodity sector goods has been long discussed in literature, results of this study defined the industries with relatively higher degree of backward integration. Certain sectors including rubber and plastic products, computer and electronic equipment, transport equipment, and textiles, exhibit higher backward participation rates (30.3%, 25.5%, 24.3%, and 26% respectively) compared to forward participation. This suggests a significant reliance on imported components, emphasizing a notable proportion of the cost structure for exports in these sectors. The base metals sector stands out with a participation rate exceeding 40%, indicating a notable position in the global value chain. The practical significance of the work relates to the defining industries that can be backward integrated to GVC.While the study discussed Kazakhstan's position in GVC and explored opportunities for defining high-end production, it underscores the need for further in-depth research to assess the potential for integrating Kazakhstan into GVC as a manufacturing site.Key words: global value chains, international markets, trade policy, forward and backward integration, trade indicators